2006
DOI: 10.1021/jp054814j
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Two Theoretical Methods to Estimate Potentiometric Titration Curves of Peptides:  Comparison with Experiment

Abstract: We compared the ability of two theoretical methods of pH-dependent conformational calculations to reproduce experimental potentiometric-titration curves of two models of peptides: Ac-K 5 -NHMe in 95% methanol (MeOH)/5% water mixture and Ac-XX(A) 7 OO-NH 2 (XAO) (where X is diaminobutyric acid, A is alanine, and O is ornithine) in water, methanol (MeOH) and dimethylsulfoxide (DMSO), respectively. The titration curve of the former was taken from the literature, and the curve of the latter was determined in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 50 publications
5
18
1
Order By: Relevance
“…This result was in agreement with an earlier small‐angle X‐ray diffraction study (SAXS) of Pande and coworkers,27 which indicated a small radius of gyration, R g = 7.4 Å, in agreement with that calculated based on our conformational studies 25, 26. Further support was gained from our potentiometric study of this peptide, in which the value of p K a1 = 2.3 is extraordinarily low, which demonstrates that all four charged groups are very close toeach other, which is possible only if there is a chain reversal 28…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…This result was in agreement with an earlier small‐angle X‐ray diffraction study (SAXS) of Pande and coworkers,27 which indicated a small radius of gyration, R g = 7.4 Å, in agreement with that calculated based on our conformational studies 25, 26. Further support was gained from our potentiometric study of this peptide, in which the value of p K a1 = 2.3 is extraordinarily low, which demonstrates that all four charged groups are very close toeach other, which is possible only if there is a chain reversal 28…”
Section: Introductionsupporting
confidence: 89%
“…In our earlier work,25, 26, 28, 29 we noticed that all‐α‐helical conformations are often formed if anti‐ROE restraints are not imposed, even though there are no ROE signals characteristic of α‐helical contacts. Including anti‐ROE restraints along with ROE restraints, therefore, is necessary.…”
Section: Methodsmentioning
confidence: 86%
“…For D9, pK a1 can be assigned to Asp15, pK a2 and pK a3 can correspond to either of the two lysine residues, and pK a4 and pK a5 can be assigned to either of the two tyrosine residues. On the basis of our earlier simulation studies of the coupling between the conformation and acidÀbase equilibria, 35 it can be noted that each of pK a2 and pK a3 (for D7 and D9), as well as pK a4 and pK a5 (for D9), as a value averaged over conformations, has contributions from either lysine (pK a2 and pK a3 ) or tyrosine (pK a4 and pK a5 ) residue. It can be seen that, for both peptides at room temperature (t = 25°C), pK a1 is lower than that of acetic acid (4.76 47 ) and pK a2 and pK a3 are significantly lower than those of n-butylamine (10.5 27 ), which can be considered a reference compound for the side chain of lysine.…”
Section: Resultsmentioning
confidence: 98%
“…It should be noted that the most populated conformations of XAO4, 5 have a bent shape, although both ends of this peptide are positively charged as for KAK; the bent shape is supported by the presence of long‐range ROE connectivities 4. As for OAD, the bent shape of XAO is confirmed by an unusually low value of p K a1 ,3 which is only 2.72 in water, compared to 8.9 for KAK and to p K a ref = 10.87 for ethylamine, which models the isolated side chain of ornithine 3. From the data of ref.…”
Section: Resultsmentioning
confidence: 81%
“…Recently,3–5 we studied the conformation of Ac‐XX‐A 7 ‐OO‐NHMe, XAO (where A, O, and X denote alanine, ornithine, and diaminobutyric acid residues, respectively) by NMR and Circular dichroism (CD) spectroscopy and theoretical calculations. Earlier, Kallenbach and coworkers6, 7 provided some experimental evidence for the presence of a polyproline II (P II ) stretch in this peptide, and also in other alanine‐based peptides8, 9; this conclusion was extended further by these researchers by stating that the P II conformation is characteristic of the unfolded state of proteins.…”
Section: Introductionmentioning
confidence: 99%